Proteinase activated receptor‐2 counterbalances the vascular effects of endothelin‐1 in fibrotic tight‐skin mice. (5th October 2016) - Roviezzo, Fiorentina; Brancaleone, Vincenzo; Mattera Iacono, Valentina; Bertolino, Antonio; De Cunto, Giovanna; Vellecco, Valentina; Lungarella, Giuseppe; Lucattelli, Monica; Cirino, Giuseppe
Abstract : Background and Purpose: The majority of the severe vascular complications in fibrosis are a consequence of a deregulated activity of mediators controlling vasomotor tone. One of the most important of these mediators is endothelin‐1 (ET‐1). Here, we have investigated the role of proteinase‐activated receptor 2 (PAR2) in the vascular dysfunction in a model of fibrosis, using tight‐skin (Tsk) mice. Experimental Approach: Aortas were collected from Tsk, transgenic over‐expressing PAR2 (TgPAR2), PAR2 deficient (PAR2 −/− ) or the corresponding WT mice. Histological and immunohistochemistry analysis for α‐smooth muscle actin, PAR2 and ET‐1 receptors were performed on aorta sections. Vascular responses to phenylephrine, ET‐1 and PAR2 activating peptide (PAR2‐AP) were assessed on aortic rings. Key Results: In aortas from Tsk mice, responses to phenylephrine were reduced, contractions to ET‐1 were increased and vasorelaxation to PAR2‐AP was enhanced. These alterations matched changes observed in whole vessel architecture such as vascular fibre re‐organization, increased collagen deposition and enhanced α‐smooth muscle actin expression. Expression of both ETA receptors and PAR2 was enhanced in Tsk mice. Antagonism of PAR2 potentiated vascular effects of ET‐1, whereas antagonism of ETA receptors increased vasorelaxation induced by PAR2‐AP. In TgPAR2 mice, responses to ET‐1 and ET‐1 plasma levels were reduced. Conversely, PAR2 −/− mice showed enhanced ET‐1 induced contraction in aortic rings and higher circulating ET‐1 levels. Conclusions and Implications: Our data show that PAR2 counterbalanced enhanced contractions to ET‐1 in aortas from Tsk mice. PAR2 could represent a possible target for novel drugs in the treatment of vascular complications in fibrosis. Linked Articles: This article is part of a themed section on Targeting Inflammation to Reduce Cardiovascular Disease Risk. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.22/issuetoc andhttp://onlinelibrary.wiley.com/doi/10.1111/bcp.v82.4/issuetoc